Pengaruh Penguasa: Analisis Perubahan Psikologi Tokoh Ki Sindujoyo dalam Naskah Serat Sindujoyo Babad Gresik - Zein, Rahmatullah; Prawoto, Eko Cahyo (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
This research discusses how the influence of the authorities influenced Ki Sindujoyo psychology in resolving conflicts in order to maintain his sovereign position. The aim of this research is to find out the causes of psychological changes in Ki Sindujoyo in resolving the conflict that occurred in the Serat Sindujoyo manuscript. The conflicts discussed include the conflict between Sultan Amangkurat and Ki Tumenggung Banyumas and Ampel Denta with Gumeno. The method used in this research is a descriptive qualitative method with an analysis of Dean G. Pruitt and Jeffrey Z. Rubin's social conflict theory in the aspect of psychological change. Data collection techniques use documentation techniques. The data is in the form of an array in the macapat song. The data source is from the book "Transferring Literacy and Translating Serat Sindujoyo" written by Amir Syarifuddin from the Mataseger community. The findings in the research show that Ki Sindujoyo role is the main key in resolving the conflict. The psychological changes that occur in Ki Sindujoyo show that the Javanese ethic is to always obey the orders of the authorities even though they know the consequences that will be received, namely succeeding in completing the task or failing to complete the task.